Kolaborasi AI dan Komunikasi Empatik dalam Penguatan Soft Skill Siswa SMK di Era Society 5.0 - Husnita, Husnita; Mukhlisiana, Lusy (Universitas Prof. Dr. Moestopo (Beragama), 2025)
The era of Society 5.0 requires the integration of Artificial Intelligence (AI) and human-centered values in vocational education. Students in Sekolah Menengah Kejuruan (SMK) must acquire strong soft skills such as effective communication, digital empathy, and self-confidence to meet industry demands. This community engagement program aims to strengthen students’ soft skills through the collaboration of AI and empathetic communication at SMK Kartika XIX-1 Bandung. The study employed a Participatory Action Research (PAR) approach involving 20 students from grades X and XI, five supervising teachers, and two facilitators from Telkom University. The program combined the AI-based Humanoid Communication 2.0 concept with training in empathetic digital communication and ethical interaction. The results indicate a 46% average improvement in students’ communication clarity, empathic response, and confidence when performing simulated professional scenarios. Students demonstrated enhanced reflective communication, polite language use, and greater assurance when engaging with AI-driven simulations. In conclusion, the integration of AI and empathetic communication effectively enhances SMK students’ soft skills and serves as a replicable model for vocational education in the Society 5.0 era.